Effects of maintaining different body positions on attentional allocation of obese and non-obese women - Garbeloto dos Santos, Fernando (Array, 2019)
Studies have shown that obese individuals may require more attentional resources to perform postural control compared to non-obese individuals. However, it is unclear if this difference in the allocation of attention can only be observed in body positions that lead to a higher level of instability. The objective of this study was to investigate if obesity affects the allocation of attention for maintaining body postures with different levels of balance demand. Ten obese women (BMI=41.7±8.5) and ten non-obese women (BMI=21.8±1.3) volunteers were assigned into two groups (M age=39.7±7.6): obese and eutrophic. The visual reaction time simultaneous with the maintenance of the body positions with different levels of balance demand (sitting, standing and unipedal stance) was used to infer the allocation of attentional resources. A longer reaction time was observed in the unipedal stance, compared to the other positions, for both groups. However, no difference was observed between the obese and eutrophic groups, for any of the body positions. The results diverge from the existing literature, showing that obesity does not affect the allocation of attention for postural control.